Another piece of the puzzle: REIT IPO underpricing after the financial crisis. Issue 3 (3rd April 2017) - Dimovski, Bill; Ratcliffe, Christopher; Keneley, Monica
Abstract : Purpose: The purpose of this paper is to investigate the underpricing of real estate investment trust (REIT) initial public offerings (IPOs) from January 2010 to June 2015, as the sector recovered from the global financial crisis. Design/methodology/approach: This study analyses the first day returns of US REIT IPOs in the post financial crisis period. The study then employs regression analysis to examine the factors that influence IPO underpricing. Findings: The study observes that underpricing, on average, is not significantly different to zero. Furthermore, the REIT IPOs examined display underperformance in the longer term. In contrast to the earlier data samples of Chen and Lu (2006), the authors do not find that underwriting costs are a direct substitute for the indirect cost of underpricing, instead the authors find that higher underwriting costs are associated with higher underpricing. Also in contrast to the mainstream underpricing literature, the data suggest larger capital raisings require higher underpricing. The authors also find that newly listed REITs provided significant excess dividend returns over the post-listing period. Practical implications: For institutional and retail investors, the results will help to further inform investment opportunities in REIT IPOs. Originality/value: This paper adds to the ongoing academic debate of the lack of underpricing in REIT IPOs relative to industrial companies. Research has shown periods of underpricing are often replaced with periods of overpricing suggesting that the pattern of behavior in REIT markets is substantially different.